1,4-Dithianes: attractive C2-building blocks for the synthesis of complex molecular architectures - Ryckaert, Bram; Demeyere, Ellen; Degroote, Frederick; Janssens, Hilde; Winne, Johan M. (Beilstein Journal of Organic Chemistry, 2023)
This review covers the synthetic applications of 1,4-dithianes, as well as derivatives thereof at various oxidation states. The selected examples show how the specific heterocyclic reactivity can be harnessed for the controlled synthesis of carbon–carbon bonds. The reactivity is compared to and put into context with more common synthetic building blocks, such as 1,3-dithianes and (hetero)aromatic building blocks. 1,4-Dithianes have as yet not been investigated to the same extent as their well-known 1,3-dithiane counterparts, but they do offer attractive transformations that can find good use in the assembly of a wide array of complex molecular architectures, ranging from lipids and carbohydrates to various carbocyclic scaffolds. This versatility arises from the possibility to chemoselectively cleave or reduce the sulfur-heterocycle to reveal a versatile C2-synthon.
Keywords: 1,4-dithianes; 1,4-dithiins; 2,3-dihydro-1,4-dithiins; heterocycles; target synthesis